Clinical Evidence Regarding Spermidine–Hyaluronate Gel as a Novel Therapeutic Strategy in Vestibulodynia Management - Filippo Murina; Alessandra Graziottin; Nicla Toni; Maria Teresa Schettino; Luca Bello; Alessandra Marchi; Barbara Del Bravo; Dania Gambini; Lara Tiranini; Rossella Elena Nappi (Pharmaceutics)
Background: Vestibulodynia (VBD) represents a summation and overlapping of trigger factors (infections, hormonal disturbances, allergies, genetic aspects, psychological vulnerability, and others) with broad individual variability. As there are no standard treatment options for VBD, the disease is still in need of appropriate therapeutic tools. Objectives: A prospective observational trial was performed to confirm the efficacy of a topical gel containing a spermidine–hyaluronate complex (UBIGEL donna™) as either a stand-alone or companion treatment through a multicenter study on a large sample population. Methods: For women with VBD (n = 154), the treatment consisted of approximately two months (4 + 4 weeks) of applications according to the posology of UBIGEL. Evaluation of symptoms was performed on relevant clinical endpoints: dyspareunia and vulvovaginal pain/burning by a visual scale (VAS); vestibular trophism by a vestibular trophic health (VeTH) score; vulvoscopy through a cotton swab test; and the level of hypertonic pelvic floor by a physical graded assessment of levator ani hypertonus. Results: A total of 154 patients treated with UBIGEL donna™ showed significant improvements across all five evaluated parameters, including pain, dyspareunia, swab test results, muscle hypertonicity, and vestibular trophism. Pain and dyspareunia scores decreased by 46.5% and 33.5%, respectively, while significant improvements were also observed in the other parameters (p < 0.0001). These improvements were consistent across various stratifications, including age and disease duration. Conclusions: The findings of the present study suggest that UBIGEL donna™ is effective in alleviating pain and dyspareunia, as well as reducing vestibular hypersensitivity in women with VBD. Although UBIGEL donna™ alone cannot serve as a comprehensive substitute for all recommended therapies, we suggest that multimodal therapy strategies may be crucial for attaining substantial improvement in any aspect of the condition.